An observation-based instrument to measure what children with disabilities do on the playground: a Rasch analysis. Issue 1 (2nd January 2019) - Grady-Dominguez, Patricia; Bundy, Anita; Ragen, Jo; Wyver, Shirley; Villeneuve, Michelle; Naughton, Geraldine; Tranter, Paul; Eakman, Aaron; Hepburn, Susan; Beetham, Kassia
ABSTRACT: The school playground provides a natural context for play observation for children of all abilities. However, play promoters interested in designing and assessing playground interventions are limited by a lack of quantitative observation tools to measure playground play sophistication for groups of children. We used Rasch analysis to evaluate the psychometric properties of a novel iPad application designed to capture observational data on the playground for children with autism spectrum disorder and/or intellectual disability. This initial investigation provides strong evidence for construct validity and moderate evidence for reliability. We suggest directions for further measure development and calibration. In conclusion, this observation tool has potential to contribute to a more nuanced understanding of playground play for children of all abilities.